The relationship of children's concern and the couple's empty-nest stress experiences with their relationship purpose - Cabarles, Irene Grace S.; Tan, Cesar T., Jr.
This corretional study aimed to find out whether the degree of children's concern for their parents and the empty-nest stress experiences of these parents have an effect on their relationship purpose.
Thesis (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Children